Research of the bending loss of S-shaped waveguides with offsets and trenches. Issue 15 (2nd September 2021) - Shang, Yuling; Guo, Wenjie; Wang, Jiaqi; Li, Chunquan; Zhao, Yamin
Abstract : S-shaped polymer waveguides are heavily exploited to connect optical components. Reducing the bending loss of S-shaped polymer waveguides is critical for low-loss and small-size optical circuits. In this paper, the S-shaped waveguide with offsets and trenches (SW-OT) is designed. The dependence of the bending loss on crucial parameters like offsets, trench locations and trench widths is analyzed by the beam propagation method. A comparison of the bending loss among standard S-bend, shifted S-bend, S-bend employing trenches and SW-OT structure is conducted. Results show that the bending loss of the SW-OT with a bending radius of 1000μm is only 0.11dB, reducing by 89.70% compared with the S-shaped waveguide with only shifts. Moreover, a dramatic reduction in the bending loss is obtained by placing trenches properly in the curved region. Therefore, the combination of offsets and trenches can effectively decrease the bending loss of low index contrast polymer S-shaped waveguides.